Mindfulness-baseret kognitiv terapi i en sundhedspsykologisk kontekst: effektstudier og kliniske betragtninger fra Enhed for Psykoonkologi og Sundhedspsykologi - Farver-Vestergaard, Ingeborg; Johannsen, Maja; Nissen, Eva Rames; O'Connor, Maja (Psyke & Logos, 2016)
Mindfulness-based cognitive therapy (MBCT) was originally developed to prevent recurrent depression, but may also be of relevance for patient groups in the field of health psychology. The present paper gives a descriptive overview of clinical trials conducted at the Unit for Psychooncology and Health Psychology (EPoS) with the overall purpose of exemplifying research-related and clinical considerations in the field. Our studies indicate that a generic application of MBCT reduces pain intensity among women treated for breast cancer, as well as depression symptoms related to spousal bereavement in old age. Furthermore, ongoing studies will yield results on the effect of disease-specific versions of MBCT adjusted to the special needs of other populations in the field of health psychology. Finally, the importance of MBCT instructor qualification is briefly discussed and specific experiences in relation to how these qualification criteria can be met are described.